Development of Animation Video Learning Media Loaded Contextual on Reaction Material Redox Using Web Apps Animaker - Ayu Taqwantari Dina Astuti; Agus Kamaludin* (Universitas Syiah Kuala, 2023)
Redox materials contain many abstract concepts. Therefore, an animated video is needed to illustrate abstract material to make it more concrete and easier to understand. This study aims to develop animated videos with contextual content on redox reaction materials using Web Apps Animaker and know the product's quality. The data collection procedure was carried out based on the 4 steps of 4D development model (define, design, develop, and disseminate). Data collection techniques used are interview, questionnaires, and product assessment. Product assessment is carried out by material experts, media experts, reviewers, and student responses. The data obtained were analyzed using qualitative and quantitative approaches. The results of product quality assessment by material experts got 92% in the very good category, media experts got 90% in the very good category, and reviewers got 95% in the very good category. Class X high school students responded positively to the product developed with a percentage of 94.5%. Based on the results of the assessment, the videos developed can be used as alternative media for student learning independently or in groups. The developed media can also help teachers to create more innovative learning